The Effect of Problem Based Learning to Critical Thinking Ability of M1 Students in Plant Biotechnology Materials - Iir Nur Choiriya; Erlia Narulita; Areerat Chuseng (BIOEDUKASI, 2019)
This study aimed to determine the effect of learning based on learning problems on students' critical thinking skills in plant biotechnology materials. This research is a quasi-experimental type using the design of "Post test and pretest, Non Equivalent Control Group Design" which consists of two experimental classes. The first experimental class used the Problem Based Learning learning model and the second class used a discussion learning model. Problem-based learning motivates students to learn independently to find information themselves from various sources, such as the environment, media and the internet. This learning trains students to think critically about contextual problems related to the material so as to improve students' cognitive abilities ranging from identifying problems, formulating hypotheses, analyzing problems, evaluating and concluding.